A Case Study of a CHP System and its Energy use Mapping. (May 2017) - Li, Jun; Laredj, Ahmed; Tian, Guohong
Abstract: This paper presents a case study of a live combined heat and power (CHP) system at the author's university campus. The system comprises a 1 MWe gas engine which is operating continuously to provide electricity, as well as a heat recovery system that recovers heat from both engine jacket water and exhaust gas to provide heat to the campus. The analysis shows that the electricity generation is stable during the year but the heat recovered fluctuates considerably at different time of the year due to the different heat demand. This results in an inefficient use of the available energy. Exergy analysis is conducted for a better understanding of the components performance of the system. An absorption chiller is finally proposed to make a better utilization of the energy and the pay-back time for the chiller is found to be approximately 22 months which is economically viable.